Imaging Manifestations of Mediastinal Fat Necrosis. (28th November 2013) - Bhatt, Malay Y.; Martínez-Jiménez, Santiago; Rosado-de-Christenson, Melissa L.; Watson, Kenneth R.; Walker, Christopher M.; Kunin, Jeffrey R.
Abstract : Mediastinal fat necrosis (MFN) or epipericardial fat necrosis, as it is commonly referred to in the literature, is a rare self-limiting cause of chest pain of unclear etiology. MFN affects previously healthy individuals who present with acute pleuritic chest pain. Characteristic computed tomography (CT) findings include a fat attenuation lesion with intrinsic and surrounding increased attenuation stranding. There is often associated thickening of the adjacent pericardium and/or pleural effusions. We present two cases of MFN manifesting as ovoid fat attenuation lesions demarcated by a soft tissue attenuation rim with intrinsic and surrounding soft tissue attenuation stranding and review the clinical and pathologic features of these lesions. Knowledge of the clinical presentation of patients with MFN and familiarity with the characteristic imaging findings of these lesions should allow radiologists to prospectively establish the correct diagnosis and suggest conservative management and follow-up.